PENGARUH GAME ONLINE TERHADAP KEMAMPUAN GRAMATIKA BAHASA JEPANG MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Alifa Jul Fardian Rosadi; Hadriana Hadriana; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack:. The ease of accessing the internet has brought a change to gaming, which was originally played offline into a game that can be done online. The purpose of this study was to find out the correlation between the usage of online gaming and Japanese grammatical capabilities. This study is limited to imperative sentence pattern in Japanese. The method used in this research is the quantitative correlation method. The instruments used were questionnaires and tests. The result of the quantitative analysis shows that there was a positive correlation between the usage of online gaming and the ability of grammar, namely in imperative setence, which is 40,4%. Based on these figures it can be concluded that the usage of online games also has an effect on improving language skills.Key Words: game online, gramatical, ability